U początków historii filmu interaktywnego (Jeffrey Shaw – Luc Courchesne – Grahame Weinbren) - Kluszczyński, Ryszard (Postscriptum Polonistyczne, 2020)
Interactive movies are a result of a dialogue between expanded cinema and the art of new media. First examples of this phenomenon were interactive film installations. Jeffrey Shaw, Luc Courchesne and Grahame Weinbren are among the precursors of this trend. Their works are fundamental to the history of interactive movies. Creations of the first two artists were of a visual and immersive character and their artistic projects resulted in creating the idea of interactive participants in film events and the concept of ‘panoramic dispositive’ as a sphere of interactive film experiences. Weinbren created a model of interactive film narration that was available in installation mode. The artists’ interactive film installations are both a continuation of previous artistic activities in the field of cinema as well as a transgression leading to new media technologies, a new concept of cinema and movie activities and new aesthetics.